Penggunaan Media Mistery Box Dengan Teknik Scramble Untuk Meningkatkan Keterampilan Membaca Siswa Kelas III SD Tanwirul Afkar - Nabilah El Rahma, Roja; Kartika Prameswari, Noviardani (IJPSE Indonesian Journal of Primary Science Education, 2025)
The use of mystery box learning media aims to improve elementary school students' reading skills. This research aims to describe the use of mistey box media with the scramble technique to improve the reading skills of grade 3 students at SD Tanwirul Afkar Surabaya using a qualitative approach. Data was collected through observation, interviews and documentation. With a total of 16 students. The results of the research show that the use of mystery box media with the scramble technique is quite effective in learning, improving students' reading skills, better understanding and increasing students' ability to work together in groups. The results of student interviews show that mystery box media can increase students' enthusiasm in reading reading texts. This conclusion emphasizes the importance of using mystery box media in learning.